System Level Methodology for Functional Verification Soc - Adamov, A.; Zaychenko, S.; Myroshnychenko, Y.; Lukashenko, O. (EWDTW, 2006)
Building a verification environment and the associated tests is a highly time-consuming process. Most project reports indicate that between 40% and 70% of the entire effort of a project is spent on verification, with 70% being much closer to the normal level for successful projects. This high level of effort indicates that the potential gains to be made with successful re-use are significant. Most projects do not start with a complete set of hardware designs available for a functional verification. Usually a design comes together as smaller blocks. Then the blocks are integrated into larger blocks, which may eventually be integrated into a system. That is reason for performing functional verification at a system level. The paper describes the system-level modeling environment for a functional verification System-on-a-Chip models. System level allow design teams to rapidly create large system-on-a-chip designs (SOCs) by integrating premade blocks that do not require any design work or verification. One of the hottest topics in embedded system design today is Electronic System Level (ESL) design. Although the idea of being able to describe a system at an abstract level has been around for a decade, only now are various parts of the design flow becoming available to make it practical. ESL describes a Systemon- chip (SoC) design in an abstract enough and fast enough way to explore the design space and provide virtual prototypes for hardware and software implementation. It is becoming a fundamental part of the design flow because we can now use it throughout the iterative design process rather than just in the early system architecting phase. ESL provides tools and methodologies that let designers describe and analyze chips on a high level of abstraction, easing the pain of designing electronic systems which would otherwise be too costly, complex or time consuming to create. The adoption of ESL can be seen in the same light as the transition to register transfer level (RTL) methodologies 10-15 years ago when complexity and time-to-market pressures obliged the industry to step up to another design level. As designs become larger with more and more IP blocks, engineers will re-use more IP. ESL methodologies that enable platform-based design will be increasingly necessary to create and test a complete system. For the most complex SoCs, IP reuse can only help up to a point. For a 40-million-gate SoC, filling even 75% of the device with existing IP leaves 10 million gates to design with original content. ESL methodologies which allow rapid creation of new blocks are likely to be leveraged by designers to quickly develop and verify original content to fill the 10 million gate void while meeting time-to- market requirements. Among the 24% percent of respondents who have implemented some form of ESL design methodology an overwhelming 87% believe ESL provides an acceptable or greater return on investment.
Keywords: device simulation; verification; system level modeling; System-on-a-Chip; SOC